2018
DOI: 10.1080/01443615.2017.1399112
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and clinical outcomes of puerperal sepsis: a prospective cohort study

Abstract: The objectives of this study were to determine the identity and antibacterial susceptibility profiles of bacteria colonising the female genital tract and blood stream and their association with clinical outcomes in women with puerperal sepsis. A prospective descriptive cohort study was conducted at two tertiary hospitals in Zimbabwe. Endocervical swabs and blood were collected for culture and susceptibility testing from 151 consecutive women who met the World Health Organisation criteria for puerperal sepsis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 17 publications
5
19
0
Order By: Relevance
“…Approximately 77.5% of culture results reviewed in this study were positive, with the most isolated germ being E. coli. This finding is similar to those revealed in other studies [21,22] which identified E. coli as the most commonly isolated organism from high vaginal swabs obtained from women with puerperal sepsis. However, these studies were limited to high vaginal swab cultures among women with puerperal sepsis and so may not reflect the true microbiological spectrum of postpartum pyrexia, compared to our study which reviewed culture results from different specimen.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately 77.5% of culture results reviewed in this study were positive, with the most isolated germ being E. coli. This finding is similar to those revealed in other studies [21,22] which identified E. coli as the most commonly isolated organism from high vaginal swabs obtained from women with puerperal sepsis. However, these studies were limited to high vaginal swab cultures among women with puerperal sepsis and so may not reflect the true microbiological spectrum of postpartum pyrexia, compared to our study which reviewed culture results from different specimen.…”
Section: Discussionsupporting
confidence: 92%
“…These infections contribute significantly to adverse maternal outcomes (Wendmagegn et al, 2018). Data from one of our previous studies and many others have shown that puerperal sepsis is the leading cause of maternal mortality in the hospital (Ngonzi et al, 2016, Majangara et al, 2018. Finding such a high incidence of SSI among post emergency Cesarean section mothers only confirms the burden as being huge, and one that needs extra attention.…”
Section: Discussionmentioning
confidence: 90%
“…A subanalysis was performed using data from a prospective cohort study that had been conducted between September 2, 2014, and July 1, 2015, among women with puerperal sepsis who were admitted to either Parirenyatwa Hospital or Harare Central Hospital in Harare, Zimbabwe. 8 Demographic data were collected using an interviewer-administered questionnaire. An endocervical swab and a blood sample were collected for microbial culture and susceptibility testing at the time of hospital admission, preferably before administration of antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…9 Information regarding any prior antibiotic administration before sample collection was captured using a case investigation form. 8 Microbial culture and susceptibility testing were performed as described previously. 8 Testing for HIV infection is routine standard of care among Zimbabwean women during the prenatal period and breastfeeding, with such testing offered using an opt-out approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation